Studi Eksperimental Kekuatan dan Perilaku Sambungan Kolom pada Struktur DfD (Design for Disassembly) - Fitriani, Intan; Sukamta, Sukamta; Nurhuda, Ilham (Department of Civil Engineering, Diponegoro University, 2015)
DfD building system is a new approach in construction. Using DfD building system can reduce construction waste and reuse building components. This research examines the strength and behaviour of DfD column connections. Two types column connections were studied.The first connection employed H shaped steel elements bolted to the column while the second connection was bolt and plate connection. The behavior of columns with connections was compared to that of without connection. This study was carried out to investigate the strength, crack patterns, and failure mechanisms of precast concrete with dry joint on DfD column structure. All specimens were subject to normal force applied with an eccentricity of 67 mm. The test results indicate that both columns with connections were able to withstand design loads. This study also confirmed that the shear strength calculation of corbel based on SNI 03-2847-2002 section 13.9 was conservative to use as the value was still smaller than that obtained from this experiment.